2013
DOI: 10.4137/ijtr.s11717
|View full text |Cite
|
Sign up to set email alerts
|

Induction of TDO2 and IDO2 in Liver by High-Fat Feeding in Mice: Discrepancies with Human Obesity

Abstract: Low-grade and chronic inflammation is elicited in white adipose tissue in human obesity. The presence of inflammatory molecules leads to an increased tryptophan catabolism through the induction of indoleamine-2,3-dioxygenase-1 (IDO1). In order to characterize the mechanisms underlying this dysregulation, we have studied 2 mouse models of obesity. Unexpectedly, we did not detect any IDO1 expression in obese or lean mice adipose tissue. In a previous study, we did not find any significant difference in the liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…In human metabolic disease, mammalian tryptophan pathway enzymes are generally upregulated, as described in Figure , but the extent to which changes in this pathway is back‐translational from human to metabolic rodent models is unclear. Intestinal IDO1 (Figure Pathway 1 to kynurenine) in HFD‐fed mice was downregulated in the present study, as reported in other tissues in DIO models . Maybe low‐grade intestinal inflammation in response to HFD does not engage IDO1 T‐cell‐mediated tolerance and antimicrobial effects .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In human metabolic disease, mammalian tryptophan pathway enzymes are generally upregulated, as described in Figure , but the extent to which changes in this pathway is back‐translational from human to metabolic rodent models is unclear. Intestinal IDO1 (Figure Pathway 1 to kynurenine) in HFD‐fed mice was downregulated in the present study, as reported in other tissues in DIO models . Maybe low‐grade intestinal inflammation in response to HFD does not engage IDO1 T‐cell‐mediated tolerance and antimicrobial effects .…”
Section: Discussionsupporting
confidence: 80%
“…Intestinal IDO1 (Figure 1 Pathway 1 to kynurenine) in HFD-fed mice was downregulated in the present study, as reported in other tissues in DIO models. 37,38 Maybe low-grade intestinal inflammation in response to HFD does not engage IDO1 T-cell-mediated tolerance and antimicrobial effects. 14…”
Section: Fold Change Expression Over Vehicle (Normalized To Ppia)mentioning
confidence: 99%
“…Kyn levels and the ratio of Kyn to Trp, which reflects IDO1, IDO2, and/or TDO2 activities, are elevated in the plasma and adipose tissue of obese women to that in lean women (Wolowczuk et al , 2012; Favennec et al , 2015). In contrast, Kyn and Kyn/Trp plasma levels are depressed in mice on high-fat diet (Poulain-Godefroy et al , 2013); in which both species are perhaps revealing the dysregulation of TDO and IDO enzymatic activities caused by an obese state. Ido1 and Ido2 gene expression is regulated in an AHR-dependent manner (Mezrich et al , 2010) and pro-inflammatory cytokines, especially INFγ (Brandacher et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ido1 −/− mice showed an even greater drop in the plasma Kyn/Trp ratio as well as a resistance to obesity (Nagano et al , 2013). Thus, IDO1, like its many roles in immune cell regulation, may be the key regulator of systemic Kyn levels in the context of obesity and obesity-associated inflammation (Watcharanurak et al , 2014), while the role of TDO2 in obesity and its regulation by glucocorticoids remain obscure (Poulain-Godefroy et al , 2013) and need to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…TDO was not found to be increased in obese individuals [ 41 ]. In contrast, a rodent model demonstrated highly upregulated TDO expression in diet-induced obesity [ 42 ]. In our cohort, plasma and urine KTR were strongly related with plasma neopterin, indicating that IFN-γ mediated IDO1 activation is a major determinant for circulating, as well as urinary, KTR levels.…”
Section: Discussionmentioning
confidence: 99%